Surface drifter data from Meteor cruise M158 (old version) - Anna Christina Hans; Peter Brandt (PANGAEA, 2021)
Surface current drifters were deployed along the equator in the Atlantic Ocean from the RV Meteor during the cruise M158, which took place between September 19 and October 26, 2019. In total, 27 CARTHE drifter and 31 Surface Velocity Program (SVP) drifters were deployed: in the central basin between 10°W and 30°W one each at every longitude and towards the edges with a slightly lower density. The CARTHE drifters are microstar drifting buoys that track currents at 1 meter beneath the surface. The data are acquired by Pacific Gyre. The utilized SVP drifters consist of five Global Drifter Program (GDP) SVPB buoys, eleven GDP SVP buoys, five ESURFMAR PG upgraded SVPB buoys, five Copernicus SVP BRST buoys and five Directional Wave Spectra Drifters from the Scripps Institution of Oceanography (SIO-DWS-D). These drifters are meant to follow the currents at 15 m depth thanks to a extquotesingleholey sock extquotesingle drogue. The drifters obtain the GPS position and transmit it along with Sea Surface Temperature data for SVPs via the satellite communication system Iridium to the lab.